The Effect of Implementing the 7E Learning Cycle Model on the Mathematical Critical Thinking Skills of Fourth-Grade Students at SDN 2 Neglasari - Alvi Aprilianti; Ejen Jenal Mutaqin; Eko Fajar Suryaningrat (Journal of Elementary Education, 2026)
This research aims to determine the effect of implementing the 7E learning cycle learning model on the mathematical critical thinking abilities of class IV students at SDN 2 Neglasari. The type of quantitative research using a quasiexperimental research design used is the non-equivalent control group design type. This research sample consisted of two groups, namely the experimental group who received learning using the 7E learning cycle model and the control group who received conventional learning. The instrument used to collect data was a mathematical critical thinking ability test in the form of essay questions. The post-test results show that it is in accordance with the hypothesis test, t = 12.875 and t table = 2.025. So at t count > t table so that Ho is rejected and Ha is accepted, meaning that the final ability of students in classes that use the 7E learning cycle learning model significantly increases students' mathematical critical thinking abilities compared to conventional learning. The implication of the research is the importance of considering appropriate learning models to improve critical mathematical thinking skills in the context of mathematics education.